ANALISIS KOMPONEN KIMIA MINYAK KAYU CENDANA HASIL PENYULINGAN METODE KUKUS - Abdul Hakim Lukman; Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
The purpose of this research is to identify the chemical components of sandalwood oil by using the Gas Chromato- graphy. The sandalwood oil was obtained by steam and water distillation of sandalwood particles which are passina and not passing through a 40 mesh screener, each for 18 and 24 hours distilling times. The identification of the peak of chemical components were done by comparing. the relatioe retention time of the peak of chemical components to that of the chemical so.lution standard, The peak area of each chemical component was calculated .by normalizaion method.The result showed that the distilling of sandalwood particles not passing 40 mesh screener for 18 and 24 hour distilling times each produced oils having as many as 26 and 28 peaks of chemical components respect wely. On the other hand, the particles passing 40 mesh screener. distilled for 18 and 24 hours exhibited as many es 28 peaks. Nevertheles. only eight chemical components could be identified from them, they are: a-pinene limonene α.santalene terpineol-4, ϐ-santalene nerolido L B-santaloL. and farnesol. Teroineo 1-4. nerolidol. B.santalol and farnesol camponents constituled the sandalwood oii: Those where usually categoried as the total santalol. The sandalwood oil distilled from the larger particles not passing 40 mesh screener for 18 and 24 hour distilling times contained the total santalol of 79. 81 a,nd 81. 45 percent, respectively. Furtheremore, the particles passing 40 mesh screener distilled for 18 and 24 hours produced oil containing 81, 74 and 80.88 percent of total santalol for each distilling time.